(untitled)
To establish the developmental stage of overwintering San Jose Scale. Quadraspidiotus perniciosus Comstock) (Homoptera: Diaspididae) specimens in Northern Italy, a monitoring progran1me canied out in Emilia-Romagna during winter 1998-99, mainly on stone fruit. According to the data collected, most of the specimens pend the greatest part of the winter in the first tag e. Only in 1narch specimens begin lo develop quite quickly tothe second and then the adult stage. The natural winter mortality recorded is significant but o i the fact that important differences exist bct, ., een years. The importance of these data for timing insecticide treat1nent also 1.vith IGRs and for choosing the most satisfactOl)" and suitable control strategy of the pest. is discussed. , number=3, journal=Bollettino di zoologia agraria e bachicoltura, year=2024, month=dic., pages=373–383